Digital Marketing Strategies in the Era of Industry 4.0 in Leveraging Data to Enhance Customer Engagement - Indrawan, Yossy Wahyu (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to identify and analyze effective digital marketing strategies in the era of Industry 4.0, focusing on the utilization of data to enhance customer engagement. The Fourth Industrial Revolution has significantly transformed business operations, particularly in the areas of data collection, analysis, and utilization. Using SWOT analysis, this research evaluates the strengths, weaknesses, opportunities, and threats associated with digital marketing strategies implemented by companies in this context. The SWOT analysis helps identify the internal and external factors influencing the success of digital marketing strategies, providing insights into how companies can optimally leverage data to build stronger relationships with their customers. The findings indicate that with the proper use of data, companies can enhance customer engagement through more personalized and relevant marketing approaches. However, challenges such as data security and consumer privacy remain critical concerns. The study concludes that digital marketing strategies supported by robust data analysis and a deep understanding of consumer behavior can provide a significant competitive advantage in the era of Industry 4.0 .